Nutraceutical and functional properties of peel, pulp, and seedextracts of six ‘Köhnü’ grape clones - Kupe,Muhammed; Karataş, Neva; Ünal, Mehmet Settar; Ercişli, Sezai; Baroň, Mojmír; Sochor, Jiří (MDPI, 2021)
Grape production has a long history in the Elazig province and surrounding vicinity andproduced grapes have been used for table consumption and also processed into traditional beverages, ̧Sıra (special non-alcoholic grape juice) and wine. In the Elazig province, the main grape cultivars are‘A ̆gın Beyazı’, ‘Öküzgözü’, ‘Bo ̆gazkere’, ‘ ̧Silfoni’, ‘Tahannebi’, and ‘Köhnü’. Among them, ‘Köhnü’cultivar is highly preferred by consumers due to its black color and perfect berry characteristics. Thecultivar has grown for centuries in different parts of Elazig and shows a great variability for mostof its morphological and biochemical characteristics. In the present study, we aimed to determinemorphological and biochemical traits in six ‘Köhnü’ clones sampled from Elazı ̆g. The cluster weightof six clones was found between 334–394 g. The highest total phenolic content was observed inseeds followed by peel and pulp samples. The seed extract of Clone 2 had the highest total phenoliccontent at 254 mg gallic acid equivalent/100 g fresh weight. The results also showed that peel, pulp,and seed samples of ‘Köhnü’ grape clones had considerable amounts of antioxidant componentsdetermined by DPPH (1,1-Diphenyl-2-picryl-hydrazyl), FRAP (ferric reducing antioxidant power),and TEAC assays and might be rich sources of natural antioxidants. Among the six ‘Köhnü’ clones,Clone 3, and Clone 6 differed from the others in respect to the highest cluster weight, the highestconcentrations of total phenolic content, and antioxidant activity. The results also implied thatall clones could be used potentially as a readily accessible source of natural antioxidants and as apossible pharmaceutical supplement.
Keywords: Biological activity; Grape; Pulp; Seed; Skin